2013
DOI: 10.1038/srep01777
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin-13 modulates voltage-gated CaV2.2 Ca2+ channels

Abstract: Integration of voltage-gated Ca2+ channels in a network of protein-interactions is a crucial requirement for proper regulation of channel activity. In this study, we took advantage of the specific properties of the yeast split-ubiquitin system to search for and characterize so far unknown interaction partners of CaV2 Ca2+ channels. We identified tetraspanin-13 (TSPAN-13) as an interaction partner of the α1 subunit of N-type CaV2.2, but not of P/Q-type CaV2.1 or L- and T-type Ca2+ channels. Interaction could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 35 publications
(45 reference statements)
0
21
0
Order By: Relevance
“…Co-immunoprecipitation was essentially performed as described previously 59 . Briefly, confluent transfected MDCK cells from two wells of a six well plate were washed with ice cold PBS and harvested by scraping using 1 ml PBS (with Roche Complete).…”
Section: Methodsmentioning
confidence: 99%
“…Co-immunoprecipitation was essentially performed as described previously 59 . Briefly, confluent transfected MDCK cells from two wells of a six well plate were washed with ice cold PBS and harvested by scraping using 1 ml PBS (with Roche Complete).…”
Section: Methodsmentioning
confidence: 99%
“…These effects counteract each other, so the final result will depend on the actual mode of channel activation under physiological conditions. More detailed analysis [44] revealed that TSPAN-13 reduced the efficiency of the coupling between activation of the voltage sensor and pore opening, thereby supporting a negative modulatory effect of this protein. RTN1 did not alter any of analyzed electrophysiological parameters.…”
Section: Modulation Of Ca V 22 Function By Novel Interaction Partnersmentioning
confidence: 92%
“…A large set of bait vectors encoding cDNA fragments of Ca V 2 Ca 2+ channel α1 subunits were constructed in our laboratory to identify, confirm, and characterize so far unknown Ca 2+ channel interaction partners [ 44 46 ]. The selection of bait constructs followed our aim to identify specific Ca V 2.2 interactors and to prove or to exclude the identified candidates as common Ca V 2-family interactors.…”
Section: Introductionmentioning
confidence: 99%
“…This binding is essential for channel tethering into presynaptic terminal. Another group used the yeast split-ubiquitin system to define the interactome of the Ca V 2.2 Ca 2+ channel α 1 subunit and identified tetraspanin-13 (TSPAN-13) (Mallmann et al 2013), reticulon 1 (RTN1), member 1 of solute carrier family 38 (SLC38), prostaglandin D2 synthase (PTGDS), and transmembrane protein 223 (TMEM223) (Mallmann et al 2019) as interaction partners of the channel. Detailed electrophysiological studies revealed that TSPAN-13, TMEM223, and, to a lesser extent, PTGDS and SLC38, negatively modulated Ca 2+ entry required for transmitter release and/or for dendritic plasticity under physiological conditions.…”
Section: Protein Complexes Formed By Ca V 22 Channelsmentioning
confidence: 99%